2018
DOI: 10.1007/s11307-018-1168-0
|View full text |Cite
|
Sign up to set email alerts
|

A Nonhuman Primate PET Study: Measurement of Brain PDE4 Occupancy by Roflumilast Using (R)-[11C]Rolipram

Abstract: Purpose: Phosphodiesterase 4 (PDE4) inhibition in the brain has been reported to improve cognitive function in animal models. Therefore, PDE4 inhibitors are one of key targets potential for drug development. Investigation of brain PDE4 occupancy would help to understand the effects of PDE4 inhibition to cognitive functions. Roflumilast is a selective phosphodiesterase type 4 (PDE4) inhibitor used clinically for severe chronic obstructive pulmonary disease, but the effects to the brain have not been well invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Apart from that, the obtained data may suggest that 30-40% of in vivo brain PDE4 occupancy, which corresponds to the clinical dose of roflumilast, might be an acceptable level of PDE4 inhibition not to induce severe nausea and emesis [48]. Further (pre-)clinical studies are required to investigate the relationship between roflumilast treatment, PDE4 occupancy in the brain, effects on cognitive domains, and occurrence of nausea and emesis [48]. For that purpose, Takano et al suggested that PET studies using subtype-specific PDE4 radioligands instead of [ 11 C]rolipram would be more effective to understand the function of the PDE4 isoforms [48].…”
Section: Recent [ 11 C]rolipram Positron Emission Tomography (Pet) Studiesmentioning
confidence: 91%
See 4 more Smart Citations
“…Apart from that, the obtained data may suggest that 30-40% of in vivo brain PDE4 occupancy, which corresponds to the clinical dose of roflumilast, might be an acceptable level of PDE4 inhibition not to induce severe nausea and emesis [48]. Further (pre-)clinical studies are required to investigate the relationship between roflumilast treatment, PDE4 occupancy in the brain, effects on cognitive domains, and occurrence of nausea and emesis [48]. For that purpose, Takano et al suggested that PET studies using subtype-specific PDE4 radioligands instead of [ 11 C]rolipram would be more effective to understand the function of the PDE4 isoforms [48].…”
Section: Recent [ 11 C]rolipram Positron Emission Tomography (Pet) Studiesmentioning
confidence: 91%
“…Roflumilast is the first PDE4 inhibitor that has been approved for treatment of severe chronic obstructive pulmonary disease (COPD) [50]. In roflumilast-treated rhesus monkeys, a reduced [ 11 C]rolipram accumulation in all brain regions, a faster washout and a decreased V T have been observed [48]. These results indicate that roflumilast is brainpenetrant and shows a dose-dependent PDE4 binding.…”
Section: Recent [ 11 C]rolipram Positron Emission Tomography (Pet) Studiesmentioning
confidence: 96%
See 3 more Smart Citations